Willingness to pay and its determinants for improved solid waste management: a case study. (16th March 2023) - Ray, Mithun; Ryngnga, Phiban Khamti; Chetia, Pompi
This study aimed to find out the probability of willingness to pay for an improved system to manage solid wastes generated in an Indian municipality using the contingent valuation method. To determine the socio-economic factors that affect the probability of willingness to pay, binary logistic regression was applied. Most of the residents are willing to pay extra money in form of direct donation or tax to get better waste management facilities and services. Although it is found that year of effective schooling, income, awareness of Swachh Bharat Abhiyan, and distance of community bin from households have positive and statistically significant effect on residents' willingness to pay, while gender played a negative and significant role in determining willingness to pay. The findings of this study could contribute to design a more sustainable system for residential waste management.